2021
DOI: 10.3390/ma14185402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neodymium and Scandium Ionic Radii on Sorption Dynamics of Amberlite IR120 and AB-17-8 Remote Interaction

Abstract: The aim of the work is to provide a comparative study of influence of ionic radii of neodymium and scandium ions on their sorption process from corresponding sulfates by individual ion exchangers Amberlite IR120, AB-17-8 and interpolymer system Amberlite IR120-AB-17-8. Experiments were carried out by using the following physicochemical methods of analysis: conductometry, pH-metry, colorimetry, and atomic-emission spectroscopy. Ion exchangers in the interpolymer system undergo remote interactions with a further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…In order to achieve an environmentally friendly separation, Jumadilov et al [ 156 ] investigated the effect of Nd(III) and Sc(III) ionic radii on their sorption process from aqueous phase using individual ion exchangers such as Amberlite IR120, AB-17-8, and an interpolymer system Amberlite IR120-AB-17-8. They reported that the initial cation and anion exchangers’ highly ionized states can be expected during their remote contact in interpolymer systems.…”
Section: Recovery Of Scandium From the Bauxite Waste (Red Mud)mentioning
confidence: 99%
“…In order to achieve an environmentally friendly separation, Jumadilov et al [ 156 ] investigated the effect of Nd(III) and Sc(III) ionic radii on their sorption process from aqueous phase using individual ion exchangers such as Amberlite IR120, AB-17-8, and an interpolymer system Amberlite IR120-AB-17-8. They reported that the initial cation and anion exchangers’ highly ionized states can be expected during their remote contact in interpolymer systems.…”
Section: Recovery Of Scandium From the Bauxite Waste (Red Mud)mentioning
confidence: 99%
“…Various adsorbents, including SBA-15, graphene oxide (GO), clay, carbon materials, chitosan and its derivatives, β-cyclodextrin, silica and nanocomposites, have been widely used for REMs recovery [13][14][15][16][17][18]. However, rare earth elements are well-known for their difficulty to isolate owing to their similar hydrated ionic radii and properties with other metal elements [19]. Therefore, the adsorption selectivity appears to be important for REMs separation [20].…”
Section: Introductionmentioning
confidence: 99%